Design Pattern Evaluation on A RESTful API Wrapper: A Case Study of Software Integration with An Internet Payment Gateway using Model-Driven Architecture - Manik, Lindung Parningotan (Journal of Information Technology and Computer Science, 2019)
A proper use of design patterns has proven to be very useful in the development of robust applications over time. In this paper, the design patterns are introduced in the early stage of the software development where model-driven architecture is used as the engineering approach. A RESTful internet payment gateway API (Application Programming Interface) wrapper is selected as the case study. At the beginning, Platform Independent Model (PIM) is created as the domain model. After that, the PIM is transformed into the Platform Specific Model (PSM). Before converting the PSM into the source code, three design patterns such as builder, observer, and factory pattern are added into the model. To evaluate the impacts of implementation, static analysis is used to examine the generated code before and after adding the design patterns. The result shows that the design decision increases cohesion, complexity, coupling, inheritance, and size metrics of the source codes.